2021
DOI: 10.21577/0100-4042.20170786
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Parameters and Relationships With Covid-19 Cases in Central South America

Abstract: This work aims to evaluate the possible relations between the confirmed daily cases of COVID-19 and the environmental parameters for the Cuiabá-Várzea Grande conurbation in the state of Mato Grosso, Brazil. The data sets used to cover the rainy-dry periods, from January to December 2020, were achieved from a database of government institutions, and processed through the Spearman correlation test. Our results showed that atmospheric pressure and fire radiative power has a significant positive correlation, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Recent COVID-19 studies in the United States show a negative correlation between humidity and cases in (30), the same as in Australia (44), and Bangladesh (29). Water (relative humidity, precipitation total, and column of water vapor) has also been shown to play a regulatory role in the transmission of COVID-19 in the southern hemisphere (27). Other studies have found winter seasonality in England and Wales (31), Germany (28) and temperate countries (45), and while the conclusion is more in favor of lower temperatures, the fact that the winters in this region have very low humidity should be noted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent COVID-19 studies in the United States show a negative correlation between humidity and cases in (30), the same as in Australia (44), and Bangladesh (29). Water (relative humidity, precipitation total, and column of water vapor) has also been shown to play a regulatory role in the transmission of COVID-19 in the southern hemisphere (27). Other studies have found winter seasonality in England and Wales (31), Germany (28) and temperate countries (45), and while the conclusion is more in favor of lower temperatures, the fact that the winters in this region have very low humidity should be noted.…”
Section: Discussionmentioning
confidence: 89%
“…To understand the role of both behavioral and environmental factors on the COVID-19, an extensive literature search was conducted (17,(22)(23)(24)(27)(28)(29)(30)(31). A.…”
Section: Methodsmentioning
confidence: 99%
“…Biomass burning is a significant anthropogenic source of aerosols, the area and the type of vegetation can influence in the composition and concentration of emitted aerosols, the heating of surface by burning process and the floatability of smoke plume makes the particulate matter affect directly the regional air quality and promote climate impacts globally [2]. Other studies in Mato Grosso and Brazil evidenced the effect of environmental parameters in the growth of viral transmission and mortality risk by respiratory diseases [3,4]. Currently, there is a scientific effort in the characterization of aerosols under ambient conditions [5].…”
Section: Introductionmentioning
confidence: 99%